2020
DOI: 10.1002/ijgo.13497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of primary Fallopian tube carcinoma: A single‐institution retrospective study of 57 cases

Abstract: Objective To analyze the clinical profile and prognosis of primary Fallopian tube cancer (PFTC) in order to improve earlier diagnosis. Methods In this retrospective study, 57 women with PFTC were assessed from 2006 to 2016. Pathology, clinical index, recurrence, and survival were analyzed. Results Mean age was 57.35 ± 9.01 years, and 73% (19/26) of the patients with early‐stage PFTC (I/II) were aged less than 60 years. Of patients who presented with abnormal vaginal bleeding, 75% (9/12) were at an early stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Risk factors for epithelial ovarian carcinoma, and thus fallopian tube carcinoma, are those that increase lifetime ovulation cycles, such as nulliparity, early menarche and late menopause 1. The most common histological subtype of PFTC is serous fallopian tube carcinoma 2 4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk factors for epithelial ovarian carcinoma, and thus fallopian tube carcinoma, are those that increase lifetime ovulation cycles, such as nulliparity, early menarche and late menopause 1. The most common histological subtype of PFTC is serous fallopian tube carcinoma 2 4…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that only about 4% of patients were diagnosed with PFTC preoperatively, 68.7% of patients were diagnosed at stage III/IV postoperatively and up to 50% of the disease was missed intraoperatively 2. Another study determined that 10.5% of patients were diagnosed with PFTC preoperatively, 80.7% were misdiagnosed with ovarian cancer and 8.8% were misdiagnosed with endometrial cancer 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] It will decrease during disease remission, and return to elevated levels in disease recurrence. Over 50% primary fallopian tube carcinoma also have elevated serum CA-125 levels, [ 13 ] so the identification of primary fallopian tube carcinoma and PLFGT can only depend on histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%